TEACHING READING USING JUMBLED SENTENCES - Ria Sakia; Ulsy Kulsum Marantika (IKIP Siliwangi, 2018)
Reading is important to getting information and the new experiences. Reading is one of the language skills because reading is an important factor that can affect one's activities to get new information and knowledge from reading activities. In this study inform the using of jumbled sentences in teaching reading. The objective of this study is to see and determine differences in student mastery in reading that use mixed sentences in class 2. The participant of this study is 29 students in tenth grade of SMK Rosma Karawang academic year 2018-2019. The method which it was applied in the quantitative method in this research. In this study, the writer applied a pre-experimental design from one group of pretest and posttest. Data analyzed in this research by paired sample test significantly p <0,05 then data analyzed and processed by a writer by using statistics data calculation of formula T-test by using SPSS v. 23 for windows.The result show there a statistically significant increase in students' reading ability.Keywords: Teaching, Reading, Jumbled Sentences